Pengembangan Model Low Cost Islamic Peer To Peer Financing Berbasis Financial Technology Untuk Akselerasi Kinerja UMKM - Satria Utama; Inayatul Ilahiyah (University of Darussalam Gontor, 2018)
Along with the development of technology, financial intermediary institutions in Indonesia also grew with the presence of technology-based financial services provider companies such as peer to peer lending company. The presence of peer to peer lending companies into an opportunity for empowerment of unbankable MSMEs that require funding. This paper examines how the business financing model aplicated by several peer to peer lending companies in Indonesia, as well as make the concept of Islamic peer to peer financing as an alternative for empowering MSMEs through business capital. This research was a qualitative research using library and field research method. The data used in the study are primary and secondary data from various literature relevant to the research discussion and. Data analysis in this research is supported by logic model theory which consist of 6 components that are situation, input, activities, output, outcomes and external factors. The results of the research showed that (1) peer to peer lending model that has been applied in Indonesia has provided access to finance effectively and efficiently, but there are still using risk fund transfer scheme and fixed cost system that will hamper the acceleration of MSMEs. (2) The concept of Islamic Peer to Peer Financing based on profit and loss sharing investment model can be one of the empowerment alternatives that use investment cooperation scheme with no risk fund transfer and fixed cost for MSMEs, so it will maximize the acceleration of MSMEs.